2014
DOI: 10.3109/13668250.2014.899566
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the important factors associated with teaching sex education to people with intellectual disability: A cross-sectional survey among paid care staff

Abstract: BackgroundSex education programs have been developed with paid care staff as sex educators. However, no information is available about whether these programs are being delivered.MethodThe aim of this study was to investigate whether paid care staff working in an organisation specialised in the care of people with mild to moderate intellectual disability teach sex education or not. An online questionnaire was therefore constructed to assess the important factors associated with teaching sex education.ResultsOf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 24 publications
3
41
0
3
Order By: Relevance
“…In this context, Ang and Lee (2016) note that teachers' discomfort with teaching sexual content, or the feeling that sexual content is essentially "inappropriate" for special education students may be related to the degree of conservatism of the society, 458 which is consistent with the conclusion of Schaafsma et al (2014) on the impact of social norms when teaching sexual health education by caregivers.…”
Section: Resultssupporting
confidence: 58%
“…In this context, Ang and Lee (2016) note that teachers' discomfort with teaching sexual content, or the feeling that sexual content is essentially "inappropriate" for special education students may be related to the degree of conservatism of the society, 458 which is consistent with the conclusion of Schaafsma et al (2014) on the impact of social norms when teaching sexual health education by caregivers.…”
Section: Resultssupporting
confidence: 58%
“…Third, previous research has shown that support staff can feel inhibited in talking about this subject (Abbott & Howarth 2007;Richards et al 2009) and that family members and other support providers set different norms for themselves (or other people without disabilities) than for people with ID (Christian et al 2002;Yool et al 2003;Swango-Wilson 2008). The results of our study show that sexuality is being talked about, but it may well be that staff feels inhibited in making agreements about supporting the individual in this area or that differences in opinions and attitudes is reflected in the absence of specific support agreements (Christian et al 2002;Yool et al 2003;Swango-Wilson 2008;Schaafsma et al 2013Schaafsma et al , 2014Schaafsma et al , 2015. A lack of support agreements in the area of sexuality may result in people with ID not being able to exercise their sexual rights, to satisfy their needs or for them to feel less able to talk about it.…”
Section: Discussionmentioning
confidence: 62%
“…; Swango‐Wilson ; Schaafsma et al . , , ). A lack of support agreements in the area of sexuality may result in people with ID not being able to exercise their sexual rights, to satisfy their needs or for them to feel less able to talk about it.…”
Section: Discussionmentioning
confidence: 99%
“…The barriers we identified are consistent with a prior study of other medical professionals. That study cited time constraints, lack of appropriate training/skills/knowledge base, and the belief that patients were either not sexually active or not interested in sex education as barriers to providing sex education counseling to patients with ID (Schaafsma et al 2014).…”
Section: Discussionmentioning
confidence: 99%